2011
DOI: 10.1128/aac.00022-11
|View full text |Cite
|
Sign up to set email alerts
|

OXA-163, an OXA-48-Related Class D β-Lactamase with Extended Activity Toward Expanded-Spectrum Cephalosporins

Abstract: Two bla OXA-48 -like-positive isolates (Klebsiella pneumoniae and Enterobacter cloacae) were recovered in Argentina in 2008 as part of a large-scale survey focused on multidrug resistance in Enterobacteriaceae. In both cases, sequencing identified ␤-lactamase OXA-163, differing from OXA-48 by a single amino substitution and a 4-amino-acid deletion. OXA-163 hydrolyzed penicillins, ceftazidime, and cefotaxime, whereas OXA-48 did not. However, OXA-163 had a much lower ability to hydrolyze carbapenems than OXA-48,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
160
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(171 citation statements)
references
References 35 publications
7
160
2
2
Order By: Relevance
“…isolate gave a negative result, which is in accordance with the fact that this OXA-48 variant is known to lack significant carbapenemase activity (28).…”
supporting
confidence: 62%
“…isolate gave a negative result, which is in accordance with the fact that this OXA-48 variant is known to lack significant carbapenemase activity (28).…”
supporting
confidence: 62%
“…First, the detection of OXA-163 outside the continent where it has been firstly identified was unexpected. This finding seems to stand against the hypothesis of OXA-163 as the equivalent in South America of OXA-48 in the Mediterranean area (15). The two patients had no history of travel abroad.…”
contrasting
confidence: 50%
“…Moreover, it is of special interest that OXA-163 has been identified in Egypt, a country of North Africa, a geographical area where OXA-48-producing Gram negatives are considered endemic (6, 9, 10). Third, both strains had much higher MICs for carbapenems than those reported by Poirel et al (15). Studies suggest that outer membrane permeability defects coupled with ESBL production can confer resistance to carbapenems (5,7,9).…”
contrasting
confidence: 41%
See 1 more Smart Citation
“…The results observed in this work could be linked to the low hydrolytic profile of OXA-163 producers, although there is still an open debate on its role as a carbapenemase. Whereas in vitro kinetic assays showed weak carbapenemase activity (11), in vivo data have suggested that OXA-163 per se could cause carbapenem treatment failure or favor the intrapatient selection of new OXA variants (12,13). a A color change from blue or green (control tube) to green/yellow or yellow (reaction tube), respectively, was interpreted as a positive result; when both tubes (control and reaction) remained either blue or green, the test was interpreted as negative.…”
mentioning
confidence: 99%